2023
DOI: 10.1590/1984-3143-ar2022-0086
|View full text |Cite
|
Sign up to set email alerts
|

CA 15-3, CRP, and LDH correlates with prognostic parameters in canine mammary neoplasms

Abstract: The identification of putative prognostic factors in canine mammary neoplasms (CMNs) has been focused on tissue-specific biomarkers, but the serum biomarkers, including cancer antigen 15-3 (CA 15-3), creactive protein (CRP), and lactate dehydrogenase (LDH) have been demonstrated to display clinical application in cases of CMNs. The aim of the study was to evaluate the levels of these serum biomarkers and their association with well-established prognostic factors in CMNs. Samples from 15 female canines with CMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Pinheiro et al (2023) [27] study, female dogs with canine mammary neoplasms were found to exhibit highest serum levels of CA 15-3. The authors of this study attempted to extend currently known diagnostic procedures of canine mammary gland tumors by introducing a new non-invasive method that effectively can be used before the onset of clinical signs, or for the purpose of postoperative diagnostics, if total bilateral mastectomy is not performed.…”
mentioning
confidence: 96%
“…Pinheiro et al (2023) [27] study, female dogs with canine mammary neoplasms were found to exhibit highest serum levels of CA 15-3. The authors of this study attempted to extend currently known diagnostic procedures of canine mammary gland tumors by introducing a new non-invasive method that effectively can be used before the onset of clinical signs, or for the purpose of postoperative diagnostics, if total bilateral mastectomy is not performed.…”
mentioning
confidence: 96%